2012
DOI: 10.1007/s10853-012-6644-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanical properties of new fibre-reinforced composites of inorganic polymers with natural wool fibres

Abstract: New fibre-reinforced composites of aluminosilicate inorganic polymer (geopolymer) with natural proteinbased fibres (carpet and Merino wool) were developed, and their mechanical properties determined. The surfaces of some of the wool fibres used in this study were chemically modified to improve their alkali resistance and reinforcing properties. The flexural strengths and failure characteristics of the composites, determined on bar-shaped samples by a three-point test method, show an approximately 40 % improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 35 publications
(44 reference statements)
2
45
0
1
Order By: Relevance
“…The use of natural fibers such as bamboo, cornhusk, wool, cotton, or flax in geopolymer matrix has been mentioned [16,17,18] and shown with promising results in the recent critical review on fiber-reinforced geopolymers [19,20]. Another study also demonstrates the surface modification of such fiber which improves its alkali resistance and results to an improved flexural strength of a reinforced metakaolin-based geopolymer as compared to that of pristine geopolymer [21]. In contrast, one recent exploratory study [22] reported no significant differences in the flexural strength between that of pristine fly ash based-geopolymer and that of geopolymer reinforced with the untreated coconut coir, cotton, or sisal fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural fibers such as bamboo, cornhusk, wool, cotton, or flax in geopolymer matrix has been mentioned [16,17,18] and shown with promising results in the recent critical review on fiber-reinforced geopolymers [19,20]. Another study also demonstrates the surface modification of such fiber which improves its alkali resistance and results to an improved flexural strength of a reinforced metakaolin-based geopolymer as compared to that of pristine geopolymer [21]. In contrast, one recent exploratory study [22] reported no significant differences in the flexural strength between that of pristine fly ash based-geopolymer and that of geopolymer reinforced with the untreated coconut coir, cotton, or sisal fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium-based geopolymer reinforced with corn husk fiber bundles resulted in 14 MPa four-point flexure strength 9 . Sodium-based geopolymer reinforced with 5 wt.% wool fiber bundles yielded 8-9 MPa three-point flexure strength 10 . Sodium-based geopolymer reinforced with 30 wt.% untreated jute weave resulted in 20.5 MPa four-point flexure strength 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium‐based geopolymer reinforced with corn husk fiber bundles resulted in 14.1 MPa four‐point flexure strength . Sodium‐based geopolymer reinforced with 5 wt% wool fiber bundles yielded 8.1–9.1 MPa three‐point flexure strength . Sodium‐based geopolymer reinforced with 30 wt% untreated jute weave resulted in 20.5 MPa four‐point flexure strength .…”
Section: Introductionmentioning
confidence: 99%